Prácticas ecológicas y manejo saludable de los residuos sólidos urbanos en la ciudad de Indiana 2022 - Ferre Pinedo, Willy Guillermo (2023)
This research was carried out in Indiana, capital of the district of the same name, upstream from the city of Iquitos; This research visualizes the ecological practices and their application for the improvement of the good sanitary management of Urban Solid Waste in the city of the study, and to give necessary contributions regarding the subject. It is a descriptive, transversal work. The results obtained show that the care of green areas and the sanitary management of household solid waste are related, due to the compliance of those in charge of this function, they keep green areas and public gardens clean of waste and weeds, with the help of the residents, so that they maintain the aesthetics and magnify the order and cleanliness of the streets. Regarding recycling activities, it is not related to solid waste management, since there are no waste segregation programs at the source, nor in the municipal dump. The cleaning of the streets is related to the sanitary management of waste, the technical team in charge complies with the collection of household solid waste from the front of the houses, containers in the market, at the established time and the sweeping of the streets is always frequent. In this city, the municipality must train people in the recycling of organic products and contribute to the agricultural producers of the area.